2009
DOI: 10.1074/jbc.m109.057950
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and Amyloid Fibril Formation Induced by Chemical Dimerization of Recombinant Prion Protein in Physiological-like Conditions

Abstract: Addition of AP20187 but not FK506 to recombinant Fv-PrP (rFv-PrP) in physiological-like conditions resulted in a rapid conformational change characterized by an increase in ␤-sheet structure and simultaneous aggregation of the protein. Aggregates were partially resistant to proteinase K and induced the conversion of soluble rFv-PrP in serial seeding experiments. As judged from thioflavin T binding and electron microscopy, aggregates converted to amyloid fibers. Aggregates were toxic to cultured cells, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…Homodimer formation has been characterized as an essential factor in the aggregation pathway of numerous proteins, such as serpin, tau, and prion protein which are all involved in protein misfolding disorders [14,25,26]. In this regard, in vitro experiments have reported the existence of a dimeric state during conversion of α-Syn from soluble monomers to oligomeric species [27].…”
Section: Introductionmentioning
confidence: 99%
“…Homodimer formation has been characterized as an essential factor in the aggregation pathway of numerous proteins, such as serpin, tau, and prion protein which are all involved in protein misfolding disorders [14,25,26]. In this regard, in vitro experiments have reported the existence of a dimeric state during conversion of α-Syn from soluble monomers to oligomeric species [27].…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that more advanced machine learning approaches, such as support vector machines, neuron networks and decision trees [21,22], would allow to combine the identified features and others to further characterise chameleon interfaces. Since, many chameleon fragments have been associated to human diseases through aggregation [4,7,17], the ability to detect a specific class of chameleon fragments, i.e. those able to form symmetric homodimer β-sheet interfaces, should contribute, not only, to a better insight about homodimerisation, but also in aggregation mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to mutations, a protein's environment may also affect its secondary structure. For example, it has been shown that the prion protein, PrP C , changes its conformation and forms aggregates when interacting with one of its isoforms PrP SC [17]. Those β-sheet aggregates are called amyloid fibrils [4] and have been linked to several human diseases including Alzheimer's, Parkinson's and Creutzfeldt-Jakob's [7].…”
Section: Introductionmentioning
confidence: 98%
“…87 A model for conversion of PrP C to amyloid based on dimeric domainswapping has been proposed, 88 inspired by the domain-swapped dimer found in the crystal structure of human PrP. 78 Most interestingly, synthetic PrP dimers were toxic to neurons both in culture 89,90 and in mouse models of prion disease, 90 and antibodies raised against tandem dimers of PrP showed anti-prion activity in vivo. 91 More recently, it was found that recombinant PrP could be converted into a toxic dimer using PMCA.…”
Section: Relevance Of the Misfolded Dimer To Prion Diseasementioning
confidence: 98%